Tanggung Jawab Negara terhadap Pencemaran Lingkungan dalam Perspektif Hak Asasi Manusia - Lutfian Ubaidillah; Firman Octhaviana Sulistiyono; Fendi Setyawan; Dominikus Rato (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Environmental pollution caused by inadequate waste management has serious impacts on public quality of life and constitutes a violation of human rights. This research aims to analyze the responsibilities of the state in addressing environmental pollution and examine its relation to the fulfillment of the right to a clean and healthy environment as guaranteed by Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia and international human rights instruments. This study employs a normative juridical method using statute and conceptual approaches. The findings reveal that the state, through central and regional governments, has a constitutional obligation to implement systematic, integrated, and sustainable waste management in order to protect citizens’ rights to a proper environment. Failure to fulfill this responsibility results in environmental degradation, increased public health risks, and human rights violations. Law enforcement, institutional strengthening, public participation, and good environmental governance are necessary to ensure a clean, healthy, and sustainable environment as a form of respect for human dignity.